Race to the poles: the thermal response of the transcriptome of two range-expanding pelagic amphipod species - Martinez-Alarcón, Diana; Held, Christoph; Harms, Lars; Auel, Holger; Hagen, Wilhelm; Havermans, Charlotte (Frontiers in Marine Science, 2024)
Introduction: Hyperiid amphipods of the genus Themisto are a key polar zooplankton group in terms of biomass and play an important role as prey for higher trophic levels. They are prone to undergo changes in abundance and distribution in the course of the ongoing environmental changes. In the Southern Ocean, Themisto gaudichaudii is predicted to expand its distribution poleward. In the Arctic, the boreal-Atlantic T. abyssorum increases in abundance, resulting in an increased competition with a genuine polar congener. It is not known, however, whether T. gaudichaudii and T. abyssorum have the potential to efficiently adapt to changing water temperatures at their current distribution range or whether they will be shifting their ranges poleward. Methods: We exposed the two Themisto species from different geographic populations to temperaturechange experiments, a cold treatment and a heat-shock treatment. After that, we carried out transcriptome sequencing to compare gene expression patterns in the different treatments and species. Results: We show that under similar heat conditions, T. gaudichaudii differentially expressed more genes (26-fold change) than T. abyssorum. Furthermore, we observed qualitative differences between genetic clusters in T. gaudichaudii. Discussion: The differences observed between genetic clusters in T. gaudichaudii suggest that evolutionary divergence can be linked to changes in the regulatory pathways involved in temperature stress. These could influence the capacity of each genetic cluster to cope differently with temperature changes. In contrast its congeneric species, T. abyssorum showed a pronounced adaptive flexibility to thermal stress; it appears to have the ability to continue its poleward expansion but may also cope with increasing temperatures in its current environments. Our findings contribute to understand the response of two range-shifting Themisto species to thermal stress in view of the environmental gradients they encounter throughout their current or future distribution ranges.